Human Communication with God through Asmaul Husna (99 Names of Allah) (Study of Asmaul Husna's Understanding in Islamic Theology) - Muntasir; Saiful Bahri; Yusfriadi; Muttaqien; Ahmad Nidal; Fadlon (Britain International for Academic Research (BIAR) Publisher, 2019)
One way to know God is by understanding the names of Allah (Asmaul Husna). Asmaul Husna is the mediator of communication used by Allah Almighty so that humans can confer to Him. This is what can be considered a channel through which humans can know God spontaneously. And it is precisely this which can move the way of discovery that is essential and opens up vast realms of spirituality to witness the light of Allah. The conclusions that can be drawn from the discussion of the understanding of Asmaul Husna in Islamic theology above are Asmaul Husna are the names of Allah that have been attributed by Allah to Himself, both those determined by Allah to Himself in Him in the Qur'an, and set by the Prophet without ta'wil (deviations), takyif (asking how), tamtsil (parable), and Tasybih (likeness). There is a difference of opinion among scholars in the determination of Asmaul Husna. The opinion of jumhur ulama that Asmaul Husna is limited by what has been determined by the Shariah. Ibn Qayyim's opinion that the determination of the attributes of perfection for Allah can be determined by what has been determined by the Shariah 'and with the five senses. Ibn Al-'Arabi views Asmaul Husna as an intermediary between God and nature, namely Asmaul Husna as the relationship between God and nature. Another view expressed by Ibn Qayyim in his book Madarijus Saalikin, that Asmaul Husna is a substance of God. This contradicts the opinion of some Mu'tazilah groups, that Asmaul Husna is a trait that is born. The opinion of the Jahmiyyah group that says Asmaul Husna is a being challenged by the Ahlus Sunnah group.